Hubungan kondisi tutupan karang dengan kepadatan megabentos di Pulau Pandan Provinsi Sumatera Barat - Raja Rahmita; Efriyeldi Efriyeldi; Thamrin Thamrin (Pelantar Press, 2022)
This research was conducted in February 2021 in the waters of Pandan Island, West Sumatra Province. This study aims to determine the relationship between coral cover and the density of megabenthos found in the Pandan Island area. The method used in this study is a survey method. Coral cover data was collected using the LIT (Line Intercept Transect) method and megabenthos data was collected using the Benthos Belt Transect method. The results showed that Pandan Island had a good percentage of coral cover. The highest density of megabenthos was trokha snails found at each station, while the lowest density was Acanthaster planci which was only found at three stations and had a percentage of coral cover that had an influence on megabenthos density. Then it was also found that there was a strong negative relationship between coral cover and non-economic megabenthos, which indicated that there was an effect of the percentage of coral cover on both economic and non-economical megabenthos.